KYIV SEISMICITY ESTIMATION BASED ON INSTRUMENTAL OBSERVATIONS AND DESTRUCTIVE EARTHQUAKES DATA - NOSENKO, O.; OMELCHENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The seismicity of Kyiv is considered in the article, the influence of historical regional earthquakes is analysed, consedering modern information received instrumentally. Also the influence of tectonic faults which pass the territory of Kyiv and near out-skirtsis consedered.